Effect of dual function metal oil palm ash catalyst in reactive distillation pyrolysis of plastics waste - Nur Aliya, Mohd Nadzri (2024)
Plastics are non-biodegradable and disposal of plastics waste poses an environmental challenge. Catalytic pyrolysis is superior to thermal pyrolysis as it uses lower temperatures and hence less energy. The performance of heterogeneous catalysts strictly depends on their structures and physicochemical properties where the heterogeneous catalysts with large specific surface areas possess more catalytic sites to enhance the overall catalytic performance. The main objective of this study is to produce liquid oil from plastic waste using dual function metal oil palm ash catalyst through catalytic pyrolysis. There are two types of catalyst involved which are nickel oil palm ash catalyst (Ni/OPA) and nickel calcium oxide oil palm ash catalyst (Ni/CaO/OPA). The catalysts were synthesized via wet impregnation method and calcined at 750◦C for four hours. The surface morphology and surface structure of the catalysts were also analyzed. Polystyrene (PS) was used to represent plastics waste. About 300g of PS that fed into the reactor with 30g of catalyst were pyrolysed at 300 - 400◦C for three hours. The pyrolysed liquid products composition and calorific value were determined using Mass Spectrometry Gas Chromatography (GC-MS) and Parr oxygen bomb 1314 calorimeter, respectively. In term of physiochemical properties of catalyst, (Ni/CaO/OPA) catalyst has higher surface area, pore volume and average pore diameter compared to (Ni/OPA) catalyst. This is because the addition of CaO in the catalyst offer a high specific surface area. It is also found that liquid oil with (Ni/CaO/OPA) catalyst has brown darker colour compared to liquid oil with (Ni/OPA) catalyst and liquid oil of PS without catalyst. The main composition for PS with (Ni/OPA) catalyst is aromatic hydrocarbon with (92.88%). PS with (Ni/OPA) sample has the highest number of C5 to C9 at (74.07%) and PS with (Ni/CaO/OPA) has the highest number of C10 to C12 at (23.77%) and PS sample has the highest number of C13 to C20 at (18.88%). In conclusion, pyrolysis on polystyrene produced higher yield and addition of dual function metal oil palm ash catalyst provide positive synergistic effect. The presence of paraffins, aromatics, and olefins in the pyrolysis oil is consistent with the composition of both diesel and gasoline. In conclusion, the application of dual metal catalyst of nickel and calcium in oil palm ash (OPA) catalyst significantly improves the cracking of hydrocarbon chain and produce better quality of liquid fuel.